ANALGESIC POWER OF THE INSOLUBLE FRACTION N-HEXANE OF MELINJO LEAVES (Gnetum gnemon L.) IN SWISS MICE (Mus musculus) - Deni Firmansyah; Renny Amelia; Sulistiorini Indriaty; Didi Rohadi; Muhammad Yani Zamzam; Rizqia Shafa Fauziah (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Melinjo (Gnetum gnemon L.) has various secondary metabolites including alkaloids, flavonoids, saponins, and tannins. In its function as an analgesic, flavonoids work to inhibit the cyclooxygenase enzyme which can reduce prostaglandin production and reduce pain. This study aims to determine the analgesic power of the n-hexane insoluble fraction of melinjo leaves (Gnetum gnemon L.) as an effective analgesic tested on male white mice (Mus musculus) and to determine the most effective dose as an analgesic. This research was experimental using test animals of 25 male white mice (Mus musculus) divided into 5 groups each consisting of 5 mice. The negative control group (CMC-Na) was 0.5%, the positive control group Mefenamic acid dose of 65 mg/KgBW, insoluble fraction hexane group (ifh) dose of 50 mg/KgBW, 100 mg/KgBW, 200 mg/KgBW. The chemical stimulus was given a dose of 400 mg/KgBW of acetic acid. The parameter measured was the number of wriggles in male white mice (Mus musculus) every 10 minutes for 60 minutes. The results of the study showed a significant difference between the negative control (CMC-Na 0.5%) and various doses of insoluble fraction hexane group, while the positive control (mefenamic acid 65 mg/KgBW) had no difference with ifh doses of 100 mg/kgBB and 200 mg/KgBW. The percentage of analgesic power of ifh at doses of 50 mg/KgBW, 100 mg/KgBW and 200 mg/KgBW was 26.64%, 57.5%, and 58.56% and the percentage of analgesic power of mefenamic acid was 69.67% ...